The secret history of the world : as laid down by the secret societies - Booth, Mark (Woodstock : The Overlook Press, 2008)
An intellectual tour of the world's lesser-known histories offers a collection of alternate views that are drawn from a premise that history has been recorded from the corrupted perspectives of its victors
In the beginning -- A short walk in the ancient woods -- The Garden of Eden -- Lucifer, the light of the world -- The gods who loved women -- The assassination of the Green King -- The age of demi-gods and heroes -- The Sphinx and the timelock -- The neolithic Alexander the Great -- The way of the wizard -- Getting to grips with matter -- The descent into darkness -- Reason--and how to rise above it -- The mysteries of Greece and Rome -- The sun god returns -- The tyranny of the fathers -- The age of Islam -- The wise demon of the Templars -- Fools for love -- The green one behind the worlds -- The Rosicrucian age -- Occult Catholicism -- The occult roots of science -- The age of Freemasonry -- The mystical-sexual revolution -- The illuminati and the rise of unreason -- The mystic death of humanity -- Wednesday, Thursday, Friday
Includes bibliographical references (p. 409-413) and index
Keywords: World history; History -- Errors, inventions, etc; Secret societies; World history; Errors; Secret societies